Discovery of 37 new pulsars through GPU-accelerated reprocessing of archival data of the Parkes multibeam pulsar survey. Issue 1 (17th February 2023) - Sengar, R; Bailes, M; Balakrishnan, V; Bernadich, M C i; Burgay, M; Barr, E D; Flynn, C M L; Stevenson, R Shannon S; Wongphechauxsorn, J
ABSTRACT: We present the discovery of 37 pulsars from ∼ 20 yr old archival data of the Parkes Multibeam Pulsar Survey using a new FFT-based search pipeline optimized for discovering narrow-duty cycle pulsars. When developing our pulsar search pipeline, we noticed that the signal-to-noise ratios of folded and optimized pulsars often exceeded that achieved in the spectral domain by a factor of two or greater, in particular for narrow duty cycle ones. Based on simulations, we verified that this is a feature of search codes that sum harmonics incoherently and found that many promising pulsar candidates are revealed when hundreds of candidates per beam even with modest spectral signal-to-noise ratios of S/N∼5–6 in higher-harmonic folds (up to 32 harmonics) are folded. Of these candidates, 37 were confirmed as new pulsars and a further 37 would have been new discoveries if our search strategies had been used at the time of their initial analysis. While 19 of these newly discovered pulsars have also been independently discovered in more recent pulsar surveys, 18 are exclusive to only the Parkes Multibeam Pulsar Survey data. Some of the notable discoveries include: PSRs J1635−47 and J1739−31, which show pronounced high-frequency emission; PSRs J1655−40 and J1843−08 belong to the nulling/intermittent class of pulsars; and PSR J1636−51 is an interesting binary system in a ∼0.75 d orbit and shows hints of eclipsing behaviour – unusual given the 340 ms rotation period of the pulsar. Our results highlight the importance of reprocessing archival pulsar surveys and using refined search techniques to increase the normal pulsar population.